2021
DOI: 10.3390/cancers13194827
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Age Drift Is Associated with Poor Outcomes and De-Differentiation in Papillary and Follicular Thyroid Carcinomas

Abstract: Alterations in global DNA methylation play a critical role in both aging and cancer, and DNA methylation (DNAm) age drift has been implicated in cancer risk and pathogenesis. In the present study, we analyzed the TCGA cohort of papillary and follicular thyroid carcinoma (PTC and FTC) for their DNAm age and association with clinic-pathological features. In 54 noncancerous thyroid (NT) samples, DNAm age was highly correlated with patient chronological age (R2 = 0.928, p = 2.6 × 10−31), but drifted to younger tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…We and others have previously observed that approximately 10-25% of PTCs carry TERT promoter mutations and that their presence predicts poor patient outcomes [16][17][18][19][20][21]. In addition, the activating BRAFV600E mutation occurs frequently in PTC tumors, and the coexistence of TERT promoter mutations with BRAFV600E has been shown to be over-represented in the most aggressive PTCs and also in cases with dedifferentiation to ATCs [17,18,22,23]. Mechanistically, Liu et al demonstrated that the hyperactive BRAF-MAP kinase cascade leads to the phosphorylation and activation of the transcription factor FOS, which in turn increases the expression of GABPB1, thereby driving formation of the GABPA-GABPB1 complex to activate mutant TERT promoter for TERT expression in a panel of human cancers including TC [24].…”
Section: Introductionmentioning
confidence: 93%
“…We and others have previously observed that approximately 10-25% of PTCs carry TERT promoter mutations and that their presence predicts poor patient outcomes [16][17][18][19][20][21]. In addition, the activating BRAFV600E mutation occurs frequently in PTC tumors, and the coexistence of TERT promoter mutations with BRAFV600E has been shown to be over-represented in the most aggressive PTCs and also in cases with dedifferentiation to ATCs [17,18,22,23]. Mechanistically, Liu et al demonstrated that the hyperactive BRAF-MAP kinase cascade leads to the phosphorylation and activation of the transcription factor FOS, which in turn increases the expression of GABPB1, thereby driving formation of the GABPA-GABPB1 complex to activate mutant TERT promoter for TERT expression in a panel of human cancers including TC [24].…”
Section: Introductionmentioning
confidence: 93%
“…Aging and cancer have been shown to share specific epigenomic alterations, and therefore the link between DNAm age and carcinogenesis has been explored ( 17 , 22 , 23 ). Both blood- and tissue-based analyses suggest that DNAmaa increases cancer susceptibility, while DNAmaa in tumors predicts poor patient outcomes in different types of cancer ( 24 33 ). However, by mapping DNA methylation, chromatin, and genome topological landscapes in colorectal cancer (CRC) and normal colon tissues, Johnstone et al.…”
Section: Introductionmentioning
confidence: 99%
“…Aging and cancer have been shown to share specific epigenomic alterations, and therefore the link between DNAm age and carcinogenesis has been explored (17,22,23). Both blood-and tissue-based analyses suggest that DNAmaa increases cancer susceptibility, while DNAmaa in tumors predicts poor patient outcomes in different types of cancer (24)(25)(26)(27)(28)(29)(30)(31)(32)(33). However, by mapping DNA methylation, chromatin, and genome topological landscapes in colorectal cancer (CRC) and normal colon tissues, Johnstone et al (34) demonstrated that age-related global hypomethylation led to chromatin reconfigurations, thereby downregulating expression of protein-coding genes, especially those promoting stem cell proliferation, epithelial-mesenchymal transition (EMT), and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Póvoa, Teixeira and colleagues reported a single-institution series of 241 PTC patients who underwent surgery and showed that TERT -promoter mutations, alone or in combination with BRAF V600E , are associated with an increased risk of developing structural disease and disease-specific mortality [ 5 ], thus providing further evidence of TERT as molecular marker of aggressivity [ 6 ]. Liu et al took an alternative approach and analyzed publicly available DNA methylation data from TCGA-profiled thyroid cancers, defining a subset of tumors with a so-called “highly drifted DNA methylation age” that tend to correlate with lower differentiation scores and might serve as a marker of the activation of certain pathways and of specific tumor characteristics [ 7 ]. Misiak and colleagues unveiled the diagnostic potential of microRNA (miRNA) deregulation in ATC, and, by profiling messenger RNA (mRNA) expression in the same specimens, their consequences for differential gene expression.…”
mentioning
confidence: 99%